2016
DOI: 10.3329/bsmmuj.v9i4.30241
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of anti-HBc antibody (IgG and IgM) among HBsAg negative apparently healthy blood donors

Abstract: <p>In person who is unable to produce HBsAg, anti-HBc antibody is a helpful marker of hepatitis B virus (HBV) infection. In the present study, we have tried to find out the incidence of anti-HBc (IgG and IgM) among blood donors HBsAg negative. People came for donating blood voluntarily or for their relatives (n = 1000) was selected on inclusion and exclusion criteria. Purposefully selected and collated samples were first tested by HBsAg ELISA of third generation reagent. HBsAg negative sample was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“… 23 , 24 Studies from Bangladesh, Italy, and Korea also reported high anti-HBc-positive status in older donors, which was attributed to the acquisition of HBV infections in earlier years when HBV was highly endemic. 30 , 31 , 32 Although the prevalence of HBV infection is still high in Nigeria, declining rates have been reported. 33 This study suggests that donors younger than 35 years may be less likely to have HBV infection or be an occult HBV carrier.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Studies from Bangladesh, Italy, and Korea also reported high anti-HBc-positive status in older donors, which was attributed to the acquisition of HBV infections in earlier years when HBV was highly endemic. 30 , 31 , 32 Although the prevalence of HBV infection is still high in Nigeria, declining rates have been reported. 33 This study suggests that donors younger than 35 years may be less likely to have HBV infection or be an occult HBV carrier.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The donor loss caused by universal anti-HBc screening was considered sustainable in low-endemic countries, though, it is generally admitted that, rejecting anti-HBc reactive blood would severely affect blood supply in medium-to-high endemic areas like Bangladesh where the prevalence of anti-HBc is high (11.7%–22.6%). [ 18 20 ] Moreover, it gives inaccurate information on HBV infection among rejected donors.…”
Section: Discussionmentioning
confidence: 99%
“…The situation has been worsened by the fact that about 5%–8% apparently healthy people of Bangladesh are chronically infected with the HBV[ 17 ] and high prevalence of anti-HBc (11.7%–22.6%) has been reported among healthy individuals. [ 18 19 20 ] Therefore, it is essential to establish a new protocol for blood screening to ensure the prevention of TAHBV infection without hampering blood availability, which is the aim of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Developing country like Bangladesh may apply core antibody for donor screening (Table 1). [33][34][35][36][37] A study from West Bengal, India, a neighboring Indian province of Bangladesh has reported that 21.3% HBsAg negative and anti-HBcpositive blood donors were harboring HBV DNA in their blood. 38 Another study from India also showed that 7.5% of HBsAg negative, anti-HBc positive blood was expressing HBV DNA.…”
Section: Hbv In Pregnant Woman Through Unsafe Blood Transfusionmentioning
confidence: 99%
“…HBsAg may absent in incubation period, 32,42 window period, 32,42 occult HBV infection, 33,43 mutant to surface antigen 32,43 and even after reactivation of resolved HBV infection. 34,42 Blood that is free of HBsAg but has high-titer core antibodies against hepatitis B surface antigen (anti-HBs) can also transmit HBV infection. However, a small proportion of donors with anti-HBc in the absence of HBsAg have circulating HBV DNA and may have a risk of infectivity (Figure 8).…”
Section: Hepatitis B Virus Screening In Pregnant Womanmentioning
confidence: 99%